2024
DOI: 10.1126/sciadv.adk8173
|View full text |Cite
|
Sign up to set email alerts
|

N-glycosylation as a eukaryotic protective mechanism against protein aggregation

Ramon Duran-Romaña,
Bert Houben,
Matthias De Vleeschouwer
et al.

Abstract: The tendency for proteins to form aggregates is an inherent part of every proteome and arises from the self-assembly of short protein segments called aggregation-prone regions (APRs). While posttranslational modifications (PTMs) have been implicated in modulating protein aggregation, their direct role in APRs remains poorly understood. In this study, we used a combination of proteome-wide computational analyses and biophysical techniques to investigate the potential involvement of PTMs in aggregation regulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…ALG5 is an enzyme involved in N-glycosylation modification and may affect the function and stability of enzymes related to milk fat synthesis, FASN, and LPL . The results of RT-qPCR and western blotting showed that ALG5 expression was upregulated in the BMECs treated with STF, and the increase was most significant under stimulation with 20 μM STF (Figure A,B).…”
Section: Resultsmentioning
confidence: 96%
“…ALG5 is an enzyme involved in N-glycosylation modification and may affect the function and stability of enzymes related to milk fat synthesis, FASN, and LPL . The results of RT-qPCR and western blotting showed that ALG5 expression was upregulated in the BMECs treated with STF, and the increase was most significant under stimulation with 20 μM STF (Figure A,B).…”
Section: Resultsmentioning
confidence: 96%
“…Glycosylation is critical for protein folding and various other cellular processes (Ruotsalainen et al, 2022). Additionally, N-glycosylation has recently been described to be protective against protein aggregation due to steric hindrance, with overrepresentation reported at the N terminus of aggregation prone regions (APRs) (Duran-Romaña et al, 2024). Considering glycosylation in the modelling of MfgE8 could provide a more comprehensive understanding of both inter-and intra-domain interactions, as well as accessibility to the putative medin cleavage sites.…”
Section: Discussionmentioning
confidence: 99%